Facing climate change and potential disaster: Lessons from Jakarta slums and the impact of modern-day individualism - Zahra, Nabila Fathia; Rahadin, Puji (ASEAN Natural Disaster Mitigation and Education Journal, 2025)
Background: Jakarta faces significant climate change risks due to rapid urbanization and insufficient infrastructure. These challenges are compounded by increasing population pressures and environmental degradation, especially in urban slums. Leveraging social capital, particularly community cooperation, can enhance resilience to climate-related impacts by promoting collective action and resource mobilization. Method: This study employed a dual-phase strategy, starting with an extensive literature review to understand the context and theoretical frameworks. It also utilized comparative analysis and systems thinking to assess the roles of social capital and community resilience in mitigating climate risks. The research incorporated a variety of credible sources and opposing viewpoints for a balanced approach. Findings: The study highlights the importance of social capital, particularly the collectivist culture of mutual cooperation (gotong royong) in Jakarta, which aids in overcoming resource limitations and fosters community cooperation. This social capital is crucial for enhancing resilience, particularly in slum and disaster-prone areas. However, urban planning issues and rising individualism present challenges to fully harnessing these resources. Conclusion: Integrating the communal practices and cultural values of gotong royong into urban planning, along with promoting social engagement, is essential for building a climate-resilient city in Jakarta. Strengthening social networks and addressing governance and infrastructure issues are key steps toward mitigating climate change impacts. Novelty/Originality of this article: This study provides a unique perspective on the role of social capital in climate resilience, specifically in Jakarta's slums, and highlights the importance of integrating cultural practices like gotong royong into urban planning to build a more resilient city. It combines insights from environmental science, sociology, and psychology to develop a comprehensive approach to climate adaptation.